The Watsons go to Birmingham -- 1963 - Curtis, Christopher Paul. (New York, NY : Bantam Doubleday Dell Books for Young Readers, 1995)
The ordinary interactions and everyday routines of the Watsons, an African American family living in Flint, Michigan, are drastically changed after they go to visit Grandma in Alabama in the summer of 1963.
Keywords: African American families -- Fiction; Brothers and sisters -- Fiction; Problem children -- Fiction; Alabama -- History -- 1951-; Bombings -- Alabama -- Birmingham -- Fiction; Afro-Americans -- Fiction; Family life -- Fiction; Prejudices -- Fiction; Brothers and sisters -- Fiction; Flint (Mich.) -- Fiction; Alabama; Alabama -- Birmingham; Since 1951; Fiction; History